Temporal Lobe Epilepsy and Surgery Selectively Alter the Dorsal, Not the Ventral, Default-Mode Network - Doucet, Gaelle E.; Skidmore, Christopher; Evans, James; Sharan, Ashwini; Sperling, Michael; Pustina, Dorian; Tracy, Joseph I. (Frontiers in Neurology, 2014)
The default-mode network (DMN) is a major resting-state network. It can be divided in 2 distinct networks: one is composed of dorsal and anterior regions (referred to as the dorsal DMN, dDMN), while the other involves the more posterior regions (referred to as the ventral DMN, vDMN). To date, no studies have investigated the potentially distinct impact of temporal lobe epilepsy (TLE) on these networks. In this context, we explored the effect of TLE and anterior temporal lobectomy (ATL) on the dDMN and vDMN. We utilized 2 resting-state fMRI sessions from left, right TLE patients (pre-/post-surgery) and normal controls (NCs, sessions 1/2). Using independent component analysis, we identified the 2 networks. We then evaluated for differences in spatial extent for each network between the groups, and across the scanning sessions. The results revealed that, pre-surgery, the dDMN showed larger differences between the three groups than the vDMN, and more particularly between right and left TLE than between the TLE patients and controls. In terms of change post-surgery, in both TLE groups, the dDMN also demonstrated larger changes than the vDMN. For the vDMN, the only changes involved the resected temporal lobe for each ATL group. For the dDMN, the left ATL group showed post-surgical increases in several regions outside the ictal temporal lobe. In contrast, the right ATL group displayed a large reduction in the frontal cortex. The results highlight that the 2 DMNs are not impacted by TLE and ATL in an equivalent fashion. Importantly, the dDMN was the more affected, with right ATL having a more deleterious effects on the dDMN than left ATL. We are the first to highlight that the dDMN more strongly bears the negative impact of TLE than the vDMN, suggesting there is an interaction between the side of pathology and DM subnetwork activity. Our findings have implications for understanding the impact TLE and subsequent ATL on the functions implemented by the distinct DMNs.